The realm of digital content regulation as a social space: Sociogenesis of moderation norms and policies on Twitch platform - Nathan Ferret (Internet Policy Review, 2025)
This article seeks to explore the socio-demographic determinants underlying the engagement of moderators and the production of content moderation norms in the French Twitch scene. Using a mixed-method approach, it highlights gender, politicisation, social class, and social vulnerability mechanisms driving these norms and their diversity across channels. Targeting a precarious and marginalised yet politicised population, Twitch is engaged by moral entrepreneurs who reinforce their social positioning through their moderation practices. The question of gender and politicisation is central, organising the positioning space of moderation practices as a realm of social distinction between two poles: on the one hand, the most prominent channels, characterised by low levels of moderation, masculinity, and depoliticisation and, on the other, the more tightly, feminine and politicised channels, serving as sources of norms embraced by platform policies. This research contributes to explaining sociologically Twitch's distinctive policy as compared to its competitors, inviting policymakers to consider how digital platforms reproduce existing social structures through their regulatory frameworks.
Keywords: 300; Content moderation; Live streaming; Digital platforms; Norms